Light-powered microrobots: Recent progress and future challenges. (February 2023) - Yang, Wenguang; Wang, Xiaowen; Wang, Zhen; Liang, Wenfeng; Ge, Zhixing
Highlights: The fabricating materials and driving mechanisms of light-powered microrobots are summarized. Latest advancements and applications of light-powered microrobots are reviewed. The challenges and future directions of light-powered microrobots for biomedical and other applications are summarized. Abstract: Light is a renewable and powerful energy source that is usually used to transmit energy and information. Microrobots driven by light with the advantages of programmable, wireless, and high resolution, are particularly attractive because of the maturing of beam modulation and optical microscopy. This review introduces state of the art light-powered microrobots that can perform mechanical motion by converting light energy into other energy sources. According to the different driving mechanisms, light-powered microrobots are divided into microrobots driven by photochemical, driven by photothermal effects, driven by photomechanical effect, and driven by optical tweezers. Furthermore, we introduce the driving mechanisms and applications of the above microrobots, discussing their advantages and limitations. At the end of this review, we look ahead to this field, pointing out the challenges and propose corresponding solutions. This review is expected to incubate innovative ideas and promote the development and application of light-powered microrobots by providing a comprehensive overview of them. And interdisciplinary approaches that combine materials science, optics, micromachining, and data science will facilitate the next generation of microrobots.